PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, STRESS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BIRO HUMAS DAN PROTOKOL SEKRETARIAT DAERAH PROVINSI PAPUA - Victor F Pasalbessy (Jurnal Ekonomi dan Bisnis, 2017)
This study aims to partially analyze the effect of Transformational Leadership, work stress and work discipline on employee performance, to determine the effect of Transformational Leadership, work stress and work discipline on employee performance simultaneously and the dominant variables influence on employee performance in the Bureau of Public Relations and Protocol. Regional Secretariat of Papua Province. The data used in this study are primary data and secondary data. The primary data needed in this study are respondents' answers to research questions related to research variables, while secondary secondary data is in the form of evidence, notes and documents that have been neatly arranged in published archives. The results of the study show that partially the Transformational Leadership and Work Discipline variables have an influence on the performance of the Public Relations and Protocol Bureau employees of the Papua Province Regional Secretariat. The variables of Transformational Leadership, Work Stress and Work Discipline simultaneously or together have an influence on the performance of the Public Relations Bureau and Protocol of the Regional Secretariat of the Papua Province. And the most dominant variable that influences the performance of the Public Relations and Protocol Bureau of the Papua Province Regional Secretariat employees is the Transformational Leadership variable.